Now we see that ( 1- sqrt x)/ (1- x)

=> (1 – sqrt x)/(1- sqrt x)*(1+ sqrt x)

=> 1/ (1+ sqrt x)

For lim x --> 1 [( 1- sqrt x)/ (1- x)]

we have lim x --> 1 [1/ ( 1+ sqrt x)]

=> 1 / (1...

## See

This Answer NowStart your **subscription** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

Now we see that ( 1- sqrt x)/ (1- x)

=> (1 – sqrt x)/(1- sqrt x)*(1+ sqrt x)

=> 1/ (1+ sqrt x)

For lim x --> 1 [( 1- sqrt x)/ (1- x)]

we have lim x --> 1 [1/ ( 1+ sqrt x)]

=> 1 / (1 + sqrt 1)

=> 1/ (1+1)

=> 1/2

**Therefore lim x --> 1 [( 1- sqrt x)/ (1- x)] = 1/2**